2016
DOI: 10.18805/lr.v0i0.7838
|View full text |Cite
|
Sign up to set email alerts
|

Stability studies in gum cluster bean genotypes

Abstract: Phenotypic stability was studied for seed yield and their component characters in fifty five genotypes of gum cluster bean under four environments during summer and Kharif 2014 at two locations. The environment + (genotypes x environment) was highly significant for all the characters indicating distinct nature of environments and the effects due to environments (linear) was highly significant for all the characters. The partitioning of G x E interaction indicated that the linear components of G x E interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The higher nutrient accumulation at initial growth stages of crop with recommended nutrients is due to availability of nutrient along with faster dry matter accumulation. These results are in close conformity with Henri et al (2008), Uma and Malathi (2009), Razvi et al (2011) in common bean, Dhakal et al (2016) and Wankhade et al (2016) in cluster bean.…”
Section: Qualitative Characterssupporting
confidence: 92%
“…The higher nutrient accumulation at initial growth stages of crop with recommended nutrients is due to availability of nutrient along with faster dry matter accumulation. These results are in close conformity with Henri et al (2008), Uma and Malathi (2009), Razvi et al (2011) in common bean, Dhakal et al (2016) and Wankhade et al (2016) in cluster bean.…”
Section: Qualitative Characterssupporting
confidence: 92%
“…Variation in the plant height was also observed by Balakumbahan et al [9] during harvesting time, it was the highest in Ct -21 (199.00 cm) followed by Ct -14 (192.97 cm) among the selected genotypes under study, and concluded that Pusa Navbahar had the highest yield and the lowest plant height among the genotypes (101.80 cm). While Wankhade et al [10], in their study observed pod length to be in the range of 88.68 to 123.34. This variation in plant height may be due to delayed days to 50 % flowering and maturity, which resulted in increased plant height.…”
Section: Plant Height (Cm)mentioning
confidence: 77%